The survey of relationship between Problemathic internet use with lonliness and satisfaction with life in internet users of Kerman - Ranjbar, Hadi; Arab, Mansour; Hatamizadeh, Maryam; Shabani, Fatemeh; Nasri, Nahid (Advances in Nursing & Midwifery, 2017)
Abstract Introduction: In recent years, the Internet use greatly increased throughout the World. In between worrying about the bad effects of this phenomenon is on the rise. This study was examined the relationship between life satisfaction, loneliness and problematic Internet use. Materials and Methods: In this cross-sectional study, 348 individuals were referred to Coffee Net in Kerman in 2011 were surveyed. Life satisfaction questionnaire, UCLA Loneliness Scale and problematic Internet use questionnaire were used. The results were analyzed using the t-test, ANOVA and Pearson correlation. Results: The relationship between problematic Internet use, loneliness and life satisfaction was negatively correlated (P <0.05). Between problematic Internet use and loneliness, there was a positive correlation (P <0.05). Marital status, sex, use of services, Yahoo and Facebook and the Internet use at home, had an impact on the problematic use of the Internet. Conclusion: The association between problematic Internet use, loneliness and life satisfaction in this study was shown. To avoid complications, it is recommended that people use the Internet with control. Keywords: Internet; Dependency; satisfaction; loneliness